Coordinated mining technology based on GIS reservoir area model and probability integral method under reservoirs - Feng Zhang; Yang Li; Shoubin Hu; Jiuxin Zhang; Zhengyi Ti; Haidong Wang (Scientific Reports)
Abstract In order to solve the tough problem of safety and reasonable exploration of coal resources under the reservoir, through developing GIS reservoir area model and the surface mining subsidence visualization system by probability integral method, it is expected to achieve the precise calculation of the working face underwater mining area, it is also proposed that optimal criterion of coordinating mining for the selection of minimum reservoir water covering area of the working face under the reservoir, the safety and reasonable working order of working face is determined. Taking the 11 working face mining area of Northern First and Southern Second mining areas under Daping coal reservoir, it can be figured out by the movement and distribution of performing dynamic simulation reservoir water: The optimal working face sequence is S2S9 $$→$$ S2S8 $$→$$ S2N7 $$→$$ S2N6 $$→$$ S2N5 $$→$$ S2N3 $$→$$ N1S5 $$→$$ S2N4 $$→$$ N1S3 $$→$$ S2N2 $$→$$ N1S4, the total area of underwater mining is 1028236.18 $$m^{2}$$ , which is 224762.29 $$m^{2}$$ less than current mining plan. The research results showed that through the movement and regulations of distribution of dynamic simulation of reservoir water, making the reasonable connection of working face under the reservoir achieved, reducing the danger degree of the recovery process of underwater working face obviously, lowering the cost of mine control water, which can provide theoretical value and guiding significance for the safe recovery of working face under the reservoir in other mining areas.